Molecular‐Level Processing of Si‐(B)‐C Materials with Tailored Nano/Microstructures. Issue 67 (8th November 2017) - Schmidt, Marion; Durif, Charlotte; Acosta, Emanoelle Diz; Salameh, Chrystelle; Plaisantin, Hervé; Miele, Philippe; Backov, Rénal; Machado, Ricardo; Gervais, Christel; Alauzun, Johan G.; Chollon, Georges; Bernard, Samuel
Abstract: The design of Si‐(B)‐C materials is investigated, with detailed insight into the precursor chemistry and processing, the precursor‐to‐ceramic transformation, and the ceramic microstructural evolution at high temperatures. In the early stage of the process, the reaction between allylhydridopolycarbosilane (AHPCS) and borane dimethyl sulfide is achieved. This is investigated in detail through solid‐state NMR and FTIR spectroscopy and elemental analyses for Si/B ratios ranging from 200 to 30. Boron‐based bridges linking AHPCS monomeric fragments act as crosslinking units, extending the processability range of AHPCS and suppressing the distillation of oligomeric fragments during the low‐temperature pyrolysis regime. Polymers with low boron contents display appropriate requirements for facile processing in solution, leading to the design of monoliths with hierarchical porosity, significant pore volume, and high specific surface area after pyrolysis. Polymers with high boron contents are more appropriate for the preparation of dense ceramics through direct solid shaping and pyrolysis. We provide a comprehensive study of the thermal decomposition mechanisms, and a subsequent detailed study of the high‐temperature behavior of the ceramics produced at 1000 °C. The nanostructure and microstructure of the final SiC‐based ceramics are intimately linked to the boron content of the polymers. B4 C/C/SiC nanocomposites can be obtained from the polymer with the highest boron content. Abstract : Ceramic structure synthesis : Si‐(B)‐C materials are designed from boron‐modified polycarbosilanes as processable and functional precursors, with detailed insight into the precursor chemistry and processing and the precursor‐to‐ceramic transformation (see figure). Materials with an original structural organization at the nanoscale and complex geometries at both micro‐ and macroscale are generated.